Modified biochar / carbon fiber / PEEK composite material and preparation method thereof

Through the combination of modified biochar/carbon fiber/PEEK composite materials and the ultrasonic stirring molding process, the problems of existing composite materials in dispersion, interface bonding strength, processing performance and thermal expansion coefficient are solved, and higher mechanical properties, conductive properties and thermal stability are achieved.

CN118580638BActive Publication Date: 2025-04-18江苏君华特种高分子材料股份有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410698984.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-04-18
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

During the preparation and application of existing chopped carbon fiber/polyether ether ketone composites, there are problems such as poor dispersion, insufficient interface bonding strength, poor processing performance and mismatch of thermal expansion coefficient.

Method used

Using modified biochar/carbon fiber/PEEK composite materials, the combination of modified biochar, chopped carbon fiber and PEEK through nitrogen-doped carbon framework is improved by using ultrasonic stirring and molding processes to improve the interfacial compatibility and mechanical properties of the material.

Benefits of technology

It significantly improves the mechanical properties, conductive properties and thermal stability of composite materials, improves interface compatibility and processing properties, and enhances the overall performance and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004870534280000071
    Figure BDA0004870534280000071
  • Figure BDA0004870534280000081
    Figure BDA0004870534280000081
Patent Text Reader

Abstract

The present invention relates to the technical field of composite materials, and in particular to a modified biochar / carbon fiber / PEEK composite material and a preparation method thereof, wherein the composite material comprises nitrogen-doped carbon skeleton modified biochar, chopped carbon fiber and PEEK; wherein the nitrogen-doped carbon skeleton modified biochar is prepared by: hydrothermally reacting a transition metal salt with an imidazole compound to obtain a nitrogen-containing MOFs precursor, mixing and grinding the precursor with a biochar material and an activator, and performing an activation reaction under a non-oxidizing atmosphere to obtain nitrogen-doped carbon skeleton modified biochar; and the composite material is prepared as follows: drying the nitrogen-doped carbon skeleton modified biochar, chopped carbon fiber and PEEK, stirring and mixing at a constant temperature in an ultrasonic wave, and then performing compression molding to obtain a modified biochar / carbon fiber / PEEK composite material. The modified composite material of the present invention has good interface compatibility, and has excellent mechanical properties, electrical conductivity and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a modified biochar / carbon fiber / PEEK composite material and a preparation method thereof. Background Art

[0002] Chopped carbon fiber / polyetheretherketone (CF / PEEK) composite is a high-performance composite material that combines the high strength and high rigidity of carbon fiber with the excellent heat resistance and chemical corrosion resistance of polyetheretherketone (PEEK). This composite material has broad application prospects in aerospace, automotive, medical and other fields. However, despite the many advantages of CF / PEEK composites, there are still some technical defects and deficiencies in their preparation and application. The preparation of chopped carbon fiber / polyetheretherketone composites generally involves the steps of mixing chopped carbon fiber with polyetheretherketone resin and hot pressing. The addition of carbon fiber powder is intended to improve the mechanical properties and thermal stability of the composite material, while polyetheretherketone provides good processing performance and chemical corrosion resistance.

[0003] The existing technology has the following problems:

[0004] 1. Dispersion problem: The compatibility between carbon fiber and polyetheretherketone resin is poor. When chopped carbon fiber and PEEK powder are directly molded, due to the high viscosity of PEEK melt, it is difficult to evenly disperse the carbon fiber in the resin, which is not conducive to improving performance.

[0005] 2. Insufficient interface bonding strength: The interface bonding strength between carbon fiber and polyetheretherketone is weak, which can easily lead to stress concentration and degradation of composite material performance.

[0006] 3. Poor processing performance: Due to the addition of carbon fiber, the viscosity of the composite material increases and the processing performance becomes worse. This may lead to defects such as holes and delamination during processing.

[0007] 4. Mismatch in thermal expansion coefficients: There is a difference in the thermal expansion coefficients of carbon fiber and polyetheretherketone, which may cause stress inside the composite material when the temperature changes, affecting the long-term stability of the composite material. Summary of the invention

[0008] In order to solve the above technical problems, a modified biochar / carbon fiber / PEEK composite material and a preparation method thereof are provided. The modified composite material of the present invention has good interface compatibility, and has excellent mechanical properties, electrical conductivity and thermal stability.

[0009] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0010] The modified biochar / carbon fiber / PEEK composite material comprises the following materials in 100% by weight:

[0011] The nitrogen-doped carbon skeleton modified biochar is 10-20%, the short-cut carbon fiber is 20-30%, and the balance is PEEK.

[0012] Furthermore, the method for preparing the nitrogen-doped carbon skeleton modified biochar comprises the following steps:

[0013] S1, dissolving a transition metal salt and an imidazole compound in a solvent, mixing them evenly and then performing a hydrothermal reaction to obtain a nitrogen-containing MOFs precursor;

[0014] S2, crushing the biomass material, carbonizing it, and then acid washing it to obtain a biochar material;

[0015] S3. Mix and grind the nitrogen-containing MOFs precursor, the biochar material and the activator, and perform an activation reaction under a non-oxidizing atmosphere to obtain nitrogen-doped carbon skeleton modified biochar.

[0016] Furthermore, the transition metal salt is one of a halide, a nitrate, an acetate, and a phosphate, wherein the transition metal is selected from one or more of chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), silver (Ag), platinum (Pt), titanium (Ti), zirconium (Zr), vanadium (V), and molybdenum (Mo);

[0017] The imidazole compound is selected from one or more of methylimidazole, hydroxymethylimidazole, aminomethylimidazole, methylimidazopyridinecarboxylic acid, methylimidazopyridine, methylimidazothiazole, methylimidazopyrazine, methylimidazoquinoline, and methylimidazopyrimidine;

[0018] The solvent is selected from one or more of methanol, ethanol, DMA, DEF, and NMP;

[0019] The biomass material is selected from one or more of coconut shells, bamboo, sugar cane, rice husks, and corn cob cores;

[0020] The activator is selected from one or more of sulfuric acid, sulfurous acid, sodium sulfide, copper sulfate, oxalic acid, lime, sulfur dioxide, lead nitrate, sodium carbonate, sodium hydroxide, lead salts, and barium salts.

[0021] Furthermore, the temperature of the hydrothermal reaction is 150-200°C and the reaction time is 10-24h;

[0022] The carbonization treatment is first heated to 500°C and kept for 1-2 hours, and then heated to 900°C and kept for 1-2 hours. The atmosphere during the carbonization treatment is selected from one or more gases selected from nitrogen, argon, helium, and oxygen.

[0023] The pickling is performed using a hydrochloric acid solution of at least 0.1 mol / L for at least 30 minutes;

[0024] The temperature of the activation reaction is 500-2000° C., the heating rate is 1-20° C. / min, and the activation time is 8-24 h.

[0025] Furthermore, the molar ratio of the transition metal salt to the imidazole compound is 1:3-4, and the amount of the solvent is 2-12 times the total weight of the transition metal salt and the imidazole compound;

[0026] The mass ratio of the nitrogen-containing MOFs precursor, the biochar material, and the activator is 1:2-3:1-2.

[0027] On the other hand, the present invention provides a method for preparing the above-mentioned modified biochar / carbon fiber / PEEK composite material, comprising the following steps: drying the nitrogen-doped carbon skeleton modified biochar, chopped carbon fiber, and PEEK, stirring and mixing them at a constant temperature in an ultrasonic wave, and then compression molding to obtain the modified biochar / carbon fiber / PEEK composite material.

[0028] Furthermore, an ultrasonic stirrer is used for the constant temperature stirring and mixing, with an ultrasonic power of 100-3000w, an ultrasonic frequency of 20-50kHz, a constant temperature of 180-200°C, and a stirring time of 30-60min. Ultrasonic waves generate strong vibrations and cavitation effects to improve the dispersion and mixing uniformity of the three components. The mixing process can be monitored to observe the mixing state of the materials. When the expected mixing effect is achieved, the stirring can be stopped.

[0029] Furthermore, the process parameters of compression molding are: first preheating treatment at a temperature of 150-200°C for 30-60 minutes. The preheating is to ensure that the material is evenly heated and reaches the required temperature. Then, compression molding is carried out at a temperature of 390-400°C and a pressure of 5-15MPa for 10-30 minutes to ensure uniform pressure. The heating rate is 10-20°C / min and the cooling rate is 5-10°C / min.

[0030] Beneficial technical effects:

[0031] 1. Enhanced mechanical properties. Nitrogen-doped carbon skeleton materials can significantly improve the mechanical properties of biochar, including strength, modulus and toughness. This enhancement effect helps to improve the overall mechanical properties of carbon fiber polyetheretherketone composites, giving them higher load-bearing capacity and better durability.

[0032] 2. Improve interfacial compatibility. Nitrogen doping can introduce polar functional groups and increase the interfacial compatibility between biochar and carbon fiber polyetheretherketone, which helps to reduce interface defects and stress concentration and improve the overall performance and stability of the composite material.

[0033] 3. Promote electron transfer. Nitrogen-doped carbon skeleton materials have good electrical conductivity and can promote electron transfer in carbon fiber polyetheretherketone composites, which helps to improve the electrical conductivity and electromagnetic shielding properties of the composites, making them have a wider application prospect in the field of electronics and electrical appliances;

[0034] 4. Improve thermal stability. Nitrogen-doped carbon skeleton materials can improve the thermal stability of biochar, allowing it to maintain stable performance in high temperature environments. This helps to improve the performance of carbon fiber polyetheretherketone composites under high temperature conditions and meet the needs of some special application scenarios. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0037] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, they are carried out in accordance with general standard requirements or general methods.

[0038] Example 1

[0039] The modified biochar / carbon fiber / PEEK composite material comprises the following materials in 100% by weight:

[0040] 5% nitrogen-doped carbon skeleton modified biochar, 30% chopped carbon fiber, and the balance PEEK (400-500 mesh powder).

[0041] The method for preparing nitrogen-doped carbon skeleton modified biochar comprises the following steps:

[0042] S1. Dissolve 13.00 g of cobalt chloride (0.1 mol) and 24.6 g of 4-methylimidazole (0.3 mol) in 200 mL of anhydrous methanol, stir ultrasonically for 10 h, mix well, perform hydrothermal reaction at 150 ° C for 12 h, centrifuge, dry, and grind to obtain a nitrogen-containing MOFs precursor;

[0043] S2. After the coconut shell is crushed to a particle size of 100 μm, it is carbonized in a tubular furnace: in a nitrogen atmosphere, the temperature is raised from room temperature to 500°C at 5°C / min for 1 hour, and then raised to 900°C for 1 hour. After the carbonization treatment is completed, it is pickled with 0.1 mol / L hydrochloric acid solution for 30 minutes, and washed with deionized water until neutral to obtain a biochar material;

[0044] S3. Mix and grind 10 g of the nitrogen-containing MOFs precursor with 20 g of the biochar material and 10 g of sodium carbonate as an activator for 1 hour, and perform activation reaction in argon at 1500° C. for 12 hours to obtain nitrogen-doped carbon skeleton modified biochar.

[0045] The preparation method of the modified biochar / carbon fiber / PEEK composite material comprises the following steps:

[0046] Prepare 50g of nitrogen-doped carbon skeleton modified biochar, 300g of chopped carbon fiber (fiber diameter 7μm, fiber length 5mm), and 650g of PEEK, and dry these materials in a nitrogen circulation oven at a temperature of 150°C for 4h, during which uniform heat distribution and nitrogen flow are ensured. After drying, let the materials cool naturally in the oven for later use;

[0047] The three materials are mixed by constant temperature ultrasonic stirring process. The dispersion and mixing uniformity of the three components are improved by strong vibration and cavitation effect generated by ultrasound. Ultrasonic stirring and mixing are carried out simultaneously under the conditions of constant temperature of 200°C, ultrasonic power of 200W and ultrasonic frequency of 20kHz. The mixing process is monitored to observe the mixing state of the materials. After the expected mixing effect is achieved, the equipment is stopped. The whole process takes about half an hour. After cooling to room temperature, the materials are taken out for use.

[0048] Compression molding: put the above-mentioned mixed materials into the plate compression mold and preheat them first, usually at 160°C. To ensure that the materials are evenly heated and reach the required temperature, the preheating time is 40 minutes. The compression temperature is set to 405°C, the heating rate is 20°C / min, and the pressure is precisely controlled to be 20MPa to ensure uniform pressure. The compression time is 10 minutes, and then cooled at a cooling rate of 10°C / min. After the compression mold is cooled to room temperature, the modified biochar / carbon fiber / PEEK composite material sheet is obtained.

[0049] Example 2

[0050] The modified biochar / carbon fiber / PEEK composite material comprises the following materials in 100% by weight:

[0051] Nitrogen-doped carbon skeleton modified biochar 5%, short-cut carbon fiber 25%, and the balance is PEEK.

[0052] The method for preparing nitrogen-doped carbon skeleton modified biochar comprises the following steps:

[0053] S1. Dissolve 13.65 g zinc chloride (0.1 mol) and 24.6 g 4-methylimidazole (0.3 mol) in 100 mL DMA, stir ultrasonically for 24 h, mix well, and then perform hydrothermal reaction at 160 ° C for 12 h. Centrifuge, dry, and grind to obtain nitrogen-containing MOFs precursor;

[0054] S2. After the coconut shell is crushed to a particle size of 200 μm, it is carbonized in a tubular furnace: using an argon atmosphere, the temperature is raised from room temperature to 400°C at 10°C / min for 2 hours and then raised to 1000°C for 1 hour. After the carbonization treatment is completed, it is pickled with 0.5 mol / L hydrochloric acid for 60 minutes, and washed with deionized water until neutral to obtain a biochar material;

[0055] S3. Mix and grind 10 g of the nitrogen-containing MOFs precursor with 30 g of the biochar material and 20 g of sodium hydroxide as an activator for 2 h, and perform activation reaction in helium at 1000° C. for 15 h to obtain nitrogen-doped carbon skeleton modified biochar.

[0056] The preparation method of the modified biochar / carbon fiber / PEEK composite material comprises the following steps:

[0057] Prepare 50g of nitrogen-doped carbon skeleton modified biochar, 250g of chopped carbon fiber (fiber diameter 7μm, fiber length 5mm), and 700g of PEEK, and dry these materials in a nitrogen circulation oven at a temperature of 180°C for 4h, during which uniform heat distribution and nitrogen flow are ensured. After drying, let the materials cool naturally in the oven for later use;

[0058] The three materials are mixed by constant temperature ultrasonic stirring process. The dispersion and mixing uniformity of the three components are improved by strong vibration and cavitation effect generated by ultrasound. Ultrasonic stirring and mixing are carried out simultaneously under the conditions of constant temperature of 160°C, ultrasonic power of 150W and ultrasonic frequency of 25kHz. The mixing process is monitored to observe the mixing state of the materials. After the expected mixing effect is achieved, the equipment is stopped. The whole process takes about half an hour. After cooling to room temperature, the materials are taken out for use.

[0059] Compression molding: put the above-mentioned mixed materials into the plate compression mold and preheat them first, usually at 180°C. To ensure that the materials are evenly heated and reach the required temperature, the preheating time is 50 minutes; the compression temperature is set to 410°C, the heating rate is 20°C / min, the pressure is precisely controlled to be 20MPa, and uniform pressure is ensured. The compression time is 15 minutes, and then cooled at a cooling rate of 10°C / min. After the compression mold is cooled to room temperature, the modified biochar / carbon fiber / PEEK composite material sheet is obtained.

[0060] Example 3

[0061] The modified biochar / carbon fiber / PEEK composite material comprises the following materials in 100% by weight:

[0062] The nitrogen-doped carbon skeleton modified biochar is 10%, the short-cut carbon fiber is 30%, and the balance is PEEK.

[0063] The method for preparing nitrogen-doped carbon skeleton modified biochar comprises the following steps:

[0064] S1. Dissolve 11.92 g zinc nitrate hexahydrate (0.04 mol) and 12.32 g 4-methylimidazole (0.15 mol) in 200 mL of DEF, stir ultrasonically for 24 h, mix well, perform hydrothermal reaction at 200 ° C for 12 h, centrifuge, dry and grind to obtain nitrogen-containing MOFs precursor;

[0065] S2. After the coconut shell is crushed to a particle size of 250 μm, it is carbonized in a tubular furnace: a mixed atmosphere of nitrogen and argon is used, the temperature is raised from room temperature to 500°C at 10°C / min and kept for 2 hours, and then raised to 900°C and kept for 2 hours. After the carbonization treatment is completed, a 0.5 mol / L hydrochloric acid solution is used for pickling for 60 minutes, and deionized water is washed to neutrality to obtain a biochar material;

[0066] S3. Mix and grind 10 g of the nitrogen-containing MOFs precursor with 30 g of the biochar material, 10 g of sodium hydroxide, and 10 g of oxalic acid for 3 h, and perform activation reaction in argon at 2000° C. for 24 h to obtain nitrogen-doped carbon skeleton modified biochar.

[0067] The preparation method of the modified biochar / carbon fiber / PEEK composite material comprises the following steps:

[0068] Prepare 100g of nitrogen-doped carbon skeleton modified biochar, 300g of chopped carbon fiber (fiber diameter 7μm, fiber length 5mm), and 600g of PEEK, and dry these materials in a nitrogen circulation oven at a temperature of 160°C for 4h, during which uniform heat distribution and nitrogen flow are ensured. After drying, let the materials cool naturally in the oven for later use;

[0069] The three materials are mixed by constant temperature ultrasonic stirring process. The dispersion and mixing uniformity of the three components are improved by strong vibration and cavitation effect generated by ultrasound. Ultrasonic stirring and mixing are carried out simultaneously under the conditions of constant temperature of 160°C, ultrasonic power of 200W and ultrasonic frequency of 30kHz. The mixing process is monitored to observe the mixing state of the materials. After the expected mixing effect is achieved, the equipment is stopped. The whole process takes about half an hour. After cooling to room temperature, the materials are taken out for use.

[0070] Compression molding: put the above-mentioned mixed materials into the plate compression mold, preheat them first, usually at 200°C. To ensure that the materials are evenly heated and reach the required temperature, the preheating time is 30 minutes; the compression temperature is set to 400°C, the heating rate is 15°C / min, the pressure is precisely controlled to be 20MPa, uniform pressure is ensured, the compression time is 15 minutes, and then cooled at a cooling rate of 10°C / min. After the compression mold is cooled to room temperature, the modified biochar / carbon fiber / PEEK composite material sheet is obtained.

[0071] Comparative Example 1

[0072] The composite material formula of this case only contains chopped carbon fibers, and the composite material ratio (keeping the PEEK percentage unchanged) and preparation are the same as those in Example 2.

[0073] Comparative Example 2

[0074] The composite material formula of this case only contains biochar material, and the composite material ratio (keeping the PEEK percentage unchanged) and preparation are the same as those in Example 2.

[0075] Comparative Example 3

[0076] The composite material formula of this case only contains biochar material and chopped carbon fiber. The composite material ratio and preparation are the same as those in Example 2, wherein the biochar material is the same as S2 in Example 2.

[0077] Comparative Example 4

[0078] The composite material formula in this case is unactivated nitrogen-doped carbon skeleton modified biochar (prepared in the same way as S1-S3 in Example 2, except that no activator is added to S3), short-cut carbon fiber, and the composite material ratio (keeping the PEEK percentage unchanged) is the same as the preparation in Example 2.

[0079] Comparative Example 5

[0080] The composite material formulation preparation in this case is the same as that in Example 2, except that the constant temperature ultrasonic stirring process is not used in the composite material preparation, but a high-speed mixer is directly used for stirring, the stirring speed is 1000 rpm, no heating is performed, and the mixing time is 1 hour.

[0081] The composite sheet (length, width and thickness 20*30*10cm) of the above case was cut horizontally from the upper, middle and lower parts, and longitudinally from the left, middle and right parts (the sampling positions between each case should be kept consistent as much as possible), and the performance differences of each area of ​​the sheet were tested. The tensile strength test standard is ISO 527, the bending strength test standard is ISO 178, and the volume resistivity test standard is ASTM D4496. The results are shown in Table 1.

[0082] Table 1 Composite material properties

[0083]

[0084]

[0085] (Note: The data format in the table is 240 / 255 / 252, which means that the minimum tensile strength is 240, the maximum tensile strength is 255, and the average tensile strength of each part is 252. / is a separator with no special meaning. The calculation method of the difference ratio is: the ratio of the absolute value of the difference between the maximum and minimum values ​​of the item to the average value. The smaller the difference ratio, the more stable the data and the better the material uniformity)

[0086] It can be seen from Table 1 that the composite material prepared by the method of the present invention has good interface compatibility, which improves the interface defects and stress concentration problems of the composite material, so that the composite material has good mechanical properties, good mechanical stability uniformity and excellent electrical conductivity.

[0087] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Modified biochar / carbon fiber / PEEK composite material, characterized in that: The following materials are included in 100% by weight: 10-20% nitrogen-doped carbon skeleton modified biochar, 20-30% chopped carbon fiber, and the balance is PEEK; The method for preparing nitrogen-doped carbon skeleton modified biochar comprises the following steps: S1, dissolving a transition metal salt and an imidazole compound in a solvent, mixing them evenly and then performing a hydrothermal reaction to obtain a nitrogen-containing MOFs precursor; S2, crushing the biomass material, carbonizing it, and then acid washing it to obtain a biochar material; S3. Mix and grind the nitrogen-containing MOFs precursor, the biochar material and the activator, and perform an activation reaction under a non-oxidizing atmosphere to obtain nitrogen-doped carbon skeleton modified biochar.

2. The modified biochar / carbon fiber / PEEK composite material according to claim 1, characterized in that: The transition metal salt is one or more of a halide, a nitrate, an acetate, and a phosphate, wherein the transition metal is one or more of chromium, manganese, iron, cobalt, nickel, copper, zinc, silver, platinum, titanium, zirconium, vanadium, and molybdenum; The imidazole compound is selected from one or more of methylimidazole, hydroxymethylimidazole, aminomethylimidazole, methylimidazopyridinecarboxylic acid, methylimidazopyridine, methylimidazothiazole, methylimidazopyrazine, methylimidazoquinoline, and methylimidazopyrimidine; The solvent is selected from one or more of methanol, ethanol, DMA, DEF, and NMP; The biomass material is selected from one or more of coconut shells, bamboo, sugar cane, rice husks, and corn cob cores; The activator is selected from one or more of sulfuric acid, oxalic acid, sodium carbonate and sodium hydroxide.

3. The modified biochar / carbon fiber / PEEK composite material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150-200°C and the reaction time is 10-24h; The carbonization treatment is first heated to 500°C and kept for 1-2 hours, and then heated to 900°C and kept for 1-2 hours. The atmosphere during the carbonization treatment is selected from one or more gases selected from nitrogen, argon, helium, and oxygen. The pickling is performed using a hydrochloric acid solution of at least 0.1 mol / L for at least 30 minutes; The temperature of the activation reaction is 500-2000° C., the heating rate is 1-20° C. / min, and the activation time is 8-24 h.

4. The modified biochar / carbon fiber / PEEK composite material according to claim 1, characterized in that: The molar ratio of the transition metal salt to the imidazole compound is 1:3-4, and the amount of the solvent is 2-12 times the total weight of the transition metal salt and the imidazole compound; The mass ratio of the nitrogen-containing MOFs precursor, the biochar material, and the activator is 1:2-3:1-2.

5. The method for preparing the modified biochar / carbon fiber / PEEK composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: drying nitrogen-doped carbon skeleton modified biochar, chopped carbon fiber and PEEK, stirring and mixing them at a constant temperature in an ultrasonic wave, and then compression molding to obtain a modified biochar / carbon fiber / PEEK composite material.

6. The preparation method according to claim 5, characterized in that: An ultrasonic stirrer is used for the constant temperature stirring and mixing, with an ultrasonic power of 100-3000W, an ultrasonic frequency of 20-50kHz, a constant temperature of 180-200°C, and a stirring time of 30-60min. Ultrasonic waves generate strong vibrations and cavitation effects to improve the dispersion and mixing uniformity of the three components. The mixing process can be monitored to observe the mixing state of the materials. When the expected mixing effect is achieved, the stirring can be stopped.

7. The preparation method according to claim 5, characterized in that: The process parameters of compression molding are: first preheat treatment at a temperature of 150-200℃ for 30-60min. The preheating is to ensure that the material is evenly heated and reaches the required temperature. Then, compression molding is carried out at a temperature of 390-400℃ and a pressure of 5-15MPa for 10-30min to ensure uniform pressure. The heating rate is 10-20℃ / min and the cooling rate is 5-10℃ / min.

Citation Information

Patent Citations

  • Preparation method and application of mixed matrix membrane doped with graphitized carbon nitride

    CN108816059A

  • Method for enhancing compounding property of carbon fibers and resin matrix

    CN109679295A